2021
DOI: 10.1038/s41598-021-93656-0
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid CNN-LSTM model for pre-miRNA classification

Abstract: AbstractmiRNAs (or microRNAs) are small, endogenous, and noncoding RNAs construct of about 22 nucleotides. Cumulative evidence from biological experiments shows that miRNAs play a fundamental and important role in various biological processes. Therefore, the classification of miRNA is a critical problem in computational biology. Due to the short length of mature miRNAs, many researchers are working on precursor miRNAs (pre-miRNAs) with longer sequences and more structural features. Pre-miRNAs can be divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 80 publications
0
28
0
2
Order By: Relevance
“…For the classification, here two Algorithms are used. They are ANN and Decision Tree Classifiers ( 10 , 25 , 28 , 39 , 40 , 42 44 ).…”
Section: Resultsmentioning
confidence: 99%
“…For the classification, here two Algorithms are used. They are ANN and Decision Tree Classifiers ( 10 , 25 , 28 , 39 , 40 , 42 44 ).…”
Section: Resultsmentioning
confidence: 99%
“…The CNN acts as a feature filter and the LSTM works as a classifier for the sequence of features coming from the CNN part. This approach is often used to classify videos by considering them as a sequence of independent frames [28]. We will present the training set generation in the next section before discussing our proposed CNN-LSTM hybrid model.…”
Section: Deep Learning Model Selectionmentioning
confidence: 99%
“…Driving recognition Camera CNN [18] From Table 1 it can be concluded that the CNN becomes one of the most useful solution in differentiating human activities. The application of the CNN has also been used in detecting the sports activity [21], classifying the posture of sows [22], surveillance video [23], violence video [24], micro RNA [25], human activity recognition [26][27][28]. The researchers in [29] conducted the research of activity recognition to help the elderly to manage their lives by themselves.…”
Section: Related Workmentioning
confidence: 99%